Proses Kolaborasi dalam Penanganan Kemiskinan: Studi Kasus pada Program Gandeng Gendong di Yogyakarta - Sofa Miftakhul Iza; Ismi Dwi Astuti Nurhaeni (Jurnal Mahasiswa Wacana Publik, 2021)
The Gandeng Gendong Program is a program issued by the Yogyakarta City government to alleviate poverty in Yogyakarta. This program emerged in 2018 and was strengthened by the issuance of Yogyakarta Mayor's Regulation Number 23 of 2018 concerning Gandeng Gendong Program in the Yogyakarta City. Gandeng Gendong is a program that is quite innovative and is included in collaborative governance because it involves 5K elements, namely City, Campus, Corporation, Village, Community in implementing the program. This research focuses on the collaborative governance process of the Gandeng Gendong program in Tegalpanggung Village with the aim of knowing the extent to which collaborative governance has been implemented related to this program. This type of research is descriptive qualitative research. The results showed that the collaborative governance process of the Gandeng Gendong Program which was carried out in Tegalpanggung Village was running quite well. This is evidenced by the formation of seven Gandeng Gendong groups that provide a variety of food and snacks to be marketed widely, both to urban villages, campuses, and online. However, there are still some obstacles, such as all elements not being able to participate in the program, the basic rules that strengthen Gandeng Gendong have not been formed, and the kelurahan has not been able to play a role as a facilitator in solving various problems that are being faced by the Gandeng Gendong group.